2008
DOI: 10.1007/s00445-008-0211-4
|View full text |Cite
|
Sign up to set email alerts
|

Geology of a complex kimberlite pipe (K2 pipe, Venetia Mine, South Africa): insights into conduit processes during explosive ultrabasic eruptions

Abstract: K2 is a steep-sided kimberlite pipe with a complex internal geology. Geological mapping, logging of drillcore and petrographic studies indicate that it comprises layered breccias and pyroclastic rocks of various grain sizes, lithic contents and internal structures. The pipe comprises two geologically distinct parts: K2 West is a layered sequence of juvenile-and lithic-rich breccias, which dip 20-45°inwards, and K2 East consists of a steep-sided pipe-like body filled with massive volcaniclastic kimberlite neste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The fill of some large diatremes can be subdivided into a number of discrete phases distinguished by variation in componentry or diamond grade (in kimberlites) that are bounded by steep contacts (e.g., White, 1991;Ross and White, 2006;Brown et al, 2008a;van Straaten et al, 2008). These different rock units were emplaced adjacent to each other in stages rather than during a major, more or less continuous pipefilling event (cf.…”
Section: Transport Within Diatremesmentioning
confidence: 99%
“…The fill of some large diatremes can be subdivided into a number of discrete phases distinguished by variation in componentry or diamond grade (in kimberlites) that are bounded by steep contacts (e.g., White, 1991;Ross and White, 2006;Brown et al, 2008a;van Straaten et al, 2008). These different rock units were emplaced adjacent to each other in stages rather than during a major, more or less continuous pipefilling event (cf.…”
Section: Transport Within Diatremesmentioning
confidence: 99%
“…It also explains how a large volume of pyroclastic debris is deposited in the vent after initial vent opening and clearing. Brown et al (2008b) argued that the proportion of ejecta which can be trapped by the vent during column collapse is in general not sufficient to account for the volume of MVK, although it may be plausible in the case of layered deposits seen at Venetia (Brown et al 2009). Porritt et al (2008b) demonstrated that a single column collapse event involving variable density material from the conduit flow, gas thrust and convective uprise zones could easily account for the volume of the MVK in the Fox kimberlite.…”
Section: Discussionmentioning
confidence: 96%
“…Analogous examples from the Venetia K02 kimberlite geology are described by Kurszlaukis and Barnett (2003) and Brown et al (2009). The K02 sidewall fan structures are zones up to about 20 m wide of country rock breccias, which have internal facies contacts dipping up to 34°(the angle of repose) away from the contact and fragment sizes that increase from sub-millimetre size to mega-lithic blocks several metres in diametre towards the contact.…”
Section: Comparison With Pit Wall Failurementioning
confidence: 97%
“…Concepts discussed in the paper are presented, such as (i) explosive preconditioning of the rock prior to collapse, (ii) under-cutting and gravitational collapse of the hanging wall, (iii) zones of breccia shearing and re-fragmentation, (iv) a possible link to a source of volcaniclastic material in K02 and (v) multiple phases of magmatic kimberlite intrusion. The image does not represent the final state of the K02 pipe; see Brown et al (2009) for sections through K02 matrix by hydrothermal circulation. The explosions are likely to have been centreed on magmatic dykes or dykes of preceding volatile fluids.…”
Section: Stage 1 Synthesis: Pre-fragmentation and Under-cuttingmentioning
confidence: 99%
See 1 more Smart Citation